A de-embedding method based on combining time and frequency domains - Wenwen Zeng; Yaoli Wang; Zhibin Wang (Scientific Reports)
Abstract This paper proposes an automatic fixture removal (AFR) de-embedding method to address the embedding error introduced by the fixture in radio frequency (RF) chip parameter testing and the cumbersome calibration process of the short-open-load-thru de-embedding method. The method uses the 2X-thru de-embedding algorithm to extract the RF fixture model. In contrast to the traditional de-embedding method, the proposed method for de-embedding uses time-domain reflectometry to draw the time-domain representation of the whole measurement system (including the fixture and the device under test), peel the impedance curve of the fixture part from the impedance curve of the whole system through the two parameters of the delay and loss of the fixture, and then convert the impedance curve of the peeled fixture part into the S parameter again. In this study, RF chip ADRF5024BCCZN, with a frequency range of 100 MHz to 44 GHz, and the design of a four-in-one fixture (one fixture with four chips) were considered. The contact mode of the RF fixture was a belt pressure plate, which had the advantages of convenient assembly and disassembly, reliable contact, accurate positioning, and reusability. A comparison of the experimental results for the AFR de-embedding method with S parameter data from Analog Devices, Inc. (ADI) showed a minimum return loss reduction of 7.95733 dB and the insertion loss is increased by 0.03216 dB to 0.76802 dB.